The impact of amalgamation of tax agencies on revenue mobilisation in Ghana: a case of Ghana Revenue Authority in Kumasi Metropolitan Area - Asamoah – Mensah, Kwame (2016)
A thesis submitted to the Department of Marketing and Corporate Strategy, School of Business, Kwame Nkrumah University of Science and Technology, in partial fulfilment of the requirements for the degree of Master of Business Administration (Strategic Management).